2022
DOI: 10.3390/v14010076
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Acute Respiratory Distress Syndrome (ARDS) and Outcomes in Hospitalized Patients with COVID-19—A Study Based on Data from the Polish National Hospital Register

Abstract: Acute respiratory distress syndrome (ARDS) is a serious complication of COVID-19. This study aimed to evaluate the prevalence of ARDS among patients hospitalized with COVID-19 in Poland as well as to characterize clinical outcomes in patients hospitalized with COVID-19-associated ARDS. This is a retrospective, secondary analysis of epidemiological data from 116,539 discharge reports on patients hospitalized with COVID-19 in Poland between March and December 2020. The overall prevalence of ARDS was 3.6%, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…During the COVID-19 pandemic, the mean duration of hospitalization increased both among patients with type 1 and type 2 diabetes. Diabetes is a risk factor for severe COVID-19, so we can hypothesize that stabilization of the clinical condition of a patient hospitalized due to diabetes was an important priority for doctors, which influenced the duration of hospitalization [ 32 ]. In this study, a wide range of lengths of hospitalization was observed (as expressed in the values of standard deviations) that may indicate markable differences in diabetic care by hospitals and geographic regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, the mean duration of hospitalization increased both among patients with type 1 and type 2 diabetes. Diabetes is a risk factor for severe COVID-19, so we can hypothesize that stabilization of the clinical condition of a patient hospitalized due to diabetes was an important priority for doctors, which influenced the duration of hospitalization [ 32 ]. In this study, a wide range of lengths of hospitalization was observed (as expressed in the values of standard deviations) that may indicate markable differences in diabetic care by hospitals and geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Data are reported using the template specified by Polish law. All discharge reports are anonymous and contain information on age, gender, date of admission, date of discharge, primary diagnosis (cause of hospitalization), secondary diagnosis (co-existing diseases), the outcome of hospitalization, and medical procedures provided during the hospitalization [ 32 ]. Data on the patients’ medical conditions were filled by the physicians and based on ICD-10 codes (10th revision of the International Statistical Classification of Diseases and Related Health Problems) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in China shows, the rate of mortality due to ARDS among COVID-19 cases was 39% [ 18 ]. The other pocket study conducted in a Polish national hospital shows the magnitude of mortality due to COVID-19 associated ARDS was 88.8% [ 19 ]. In addition, the health facilities are overburdened and increased utilization of critical care services by COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Severely ill patients can rapidly progress to acute respiratory distress syndrome within a week. This is observed in 3.6-17% of hospitalized patients with global mortality ranging from 3.4% to 88% for all COVID-19 cases [13][14][15][16][17][18]. Furthermore, several hospitalized COVID-19 patients develop sepsis, which is triggered by the host's immune response to SARS-CoV-2 and leads to an aberrant inflammatory reaction or so-called cytokine storm [19].…”
Section: Introductionmentioning
confidence: 99%